Physical measures of the carcass and the chemical composition of Longissimus dorsi muscle of Alentejano pigs between 70 and 110 kg LW - Neves J.A.; Freitas A.; Martins J.M.; Tirapicos Nunes J. (7th International Symposium on the Mediterranean Pig, 2012)
The aim of this work was to determine the relationship between physical measures from the subcutaneous tissue and Longissimus dorsi (LD) muscle (area, depth, and width measured between the 3rd and 4th lumbar vertebrae, at the last rib, and between the 3rd and 4th last ribs) and the chemical composition of LD at 70, 80, 90, 100, and 110 kg LW. The content of water, protein, neutral and polar lipids, total and soluble collagen, and total pigments, were determined. Globally, the measures taken and the chemical composition were not affected between 70 and 110 kg, except for the LD depth and width at the 3rd-4th lumbar vertebrae. At 70 kg, the LD depth was greater than at 110 kg (3.77 vs 2.75 cm, P<0.05) and the width was smaller (8.14 vs 9.82 cm, P<0.05). In conclusion, from 70 to 110 kg: (i) the morphological changes in the lumbar region were due mainly to the width dimension, with no impact on the chemical composition of the muscle; and (ii) the chemical composition did not change drastically, even though the amount of intramuscular fat increased slightly between 70 and 110 kg (5.32 and 6.67%, respectively) suggesting an early intramuscular fat deposition.
7. International Symposium on the Mediterranean Pig, 2010/10/14-16, Córdoba (Spain)